Impact of Lianhua Qingwen on viral shedding in omicron mild/asymtomatic patients: a real-world study - Gai, Xiaoyan; Yan, Changjian; Wu, Chaoling; Duan, Zhonghui; Fan, Jiarun; Yuan, Shengren; Yang, Ping; Bao, Fang; Jing, Hongmei; Cai, Chao; Ma, Yingmin; Zhang, Weilong; et al. (Frontiers in Medicine, 2024)
Background Lianhuaqingwen (LHQW), a traditional Chinese medicine comprised of 13 herbal extracts renowned for their robust heat-clearing and detoxifying properties, has gained widespread utilization in China but has yet to garner similar recognition abroad. It is believed to exhibit efficacy in ameliorating symptoms in individuals afflicted with coronavirus disease 2019 (COVID-19). However, the precise impact of LHQW on viral shedding (VS), particularly in the context of mild or asymptomatic infections caused by the Omicron BF.4/5 or BF.7 variants of COVID-19, remained inadequately elucidated. Consequently, a real-world study was conducted, involving patients diagnosed with COVID-19, with the primary objective of ascertaining the effectiveness of LHQW in this specific clinical context. Methods We conducted an investigation on Omicron-infected patients through a single-center, propensity score-matched real-world study conducted at Xiaotangshan Fangcang Hospital from May to November 2022. A total of 3,368 COVID-19 patients were enrolled in the study, all of whom presented mild or asymptomatic infections caused by either BF.4/5 or BF.7 strains of the virus. Demographic and clinical data were systematically collected from medical records. Patients were allocated to receive treatment with LHQW (designated as the treatment group) or received no LHQW treatment (designated as the not-treated/no-treatment group). Viral load was quantified utilizing quantitative real-time PCR (qPCR), and the duration of VS was defined as the time interval between the initial negative test result and the date of COVID-19 diagnosis or symptom onset. Results The study encompassed a cohort of 3,368 patients, and following propensity score matching, a subset of 296 patients was meticulously chosen for subsequent analysis. Notably, baseline characteristics exhibited disparities between the treatment and not-treated/no-treatment groups. However, post-matching, these characteristics achieved a commendable level of comparability. Our findings unequivocally demonstrated that there existed no statistically significant disparity in VS. This holds true when comparing patients subjected to LHQW treatment against those not administered LHQW, as well as when contrasting individuals presenting asymptomatic and mild COVID-19 manifestations. Conclusion No statistically significant difference in VS was observed between patients who underwent LHQW treatment and those who did not. Additional investigations are imperative to provide a comprehensive assessment of LHQW’s efficacy, particularly in patients afflicted with severe COVID-19 or those infected with viral strains distinct from BF.4/5 or BF.7.